2008
DOI: 10.1016/j.nuclphysb.2007.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Competing orders in one-dimensional half-integer fermionic cold atoms: A conformal field theory approach

Abstract: The physical properties of arbitrary half-integer spins F = N − 1/2 fermionic cold atoms loaded into a one-dimensional optical lattice are investigated by means of a conformal field theory approach. We show that for attractive interactions two different superfluid phases emerge for F ≥ 3/2: A BCS pairing phase, and a molecular superfluid phase which is formed from bound-states made of 2N fermions. In the low-energy approach, the competition between these instabilities and charge-density waves is described in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 87 publications
5
51
0
Order By: Relevance
“…We found that these are likely to be stabilized in systems which display an enlarged symmetry at low-energies and are associated with emergent duality symmetries in the spin sector. Our results are in agreement with previous findings for three types of bound-states that were identified in the attractive SU(N) Hubbard model with N = 3 and N = 4 [15,[18][19][20][21] as well as for SP (N) models [12,14,16,17] in such a situation is then SU(q) × SO(j). For odd j the bound-state has a charge q and the unit of current is j.…”
Section: Conclusion and Open Questionssupporting
confidence: 93%
See 3 more Smart Citations
“…We found that these are likely to be stabilized in systems which display an enlarged symmetry at low-energies and are associated with emergent duality symmetries in the spin sector. Our results are in agreement with previous findings for three types of bound-states that were identified in the attractive SU(N) Hubbard model with N = 3 and N = 4 [15,[18][19][20][21] as well as for SP (N) models [12,14,16,17] in such a situation is then SU(q) × SO(j). For odd j the bound-state has a charge q and the unit of current is j.…”
Section: Conclusion and Open Questionssupporting
confidence: 93%
“…Performing the necessary OPE and averaging over the spin degrees of freedom we find, for the bound-state wave function and the density operator, the corrections to (IV. 16) and (IV.17)…”
Section: N Even: P-wave Pairingmentioning
confidence: 90%
See 2 more Smart Citations
“…,N − 1) describe the long-distance correlations of σ k r at the critical point [114]. In the context of cold atoms, the Z N CFT is also very useful to map out the zero-temperature phase diagram of general 1D higher-spin cold fermions [14,62,116].…”
Section: Nondegenerate Mott-insulating Phasesmentioning
confidence: 99%